Evictionism, Pro-Life and Pro-Choice - Block, Walter (Roczniki Filozoficzne, 2025)
Private property rights and evictions are two sides of the same coin. You can’t have one without the other. If you really own something, anything, you have the right to evict trespassers. If you cannot evict them, then, to that extent, you do not fully, really, own the property in question. The present paper will apply this insight to abortion, regarding the pro-life, pro-choice and evictionism positions on this matter.